Processos de subjetivação, poder disciplinar e trabalho docente no Grupo Escolar Professor Manoel Antonio de Castro (1940 – 1970) - PIMENTEL, Glaybe Antonio Sousa (Universidade Federal do Pará, 2012)
This work has for purpose to discuss the School Groups as space to become subjective and cultivation of the power to discipline; to analyze the characteristic aspects expressed in the biopolitic established by the State starting from the curriculum proposed by the educational reforms contained in de Federal Constitution of 1946, in the Ordinance-law no. 8529 and 8530 of January of 1946, in de Federal Constitution of 1967 and in the Law of Guidelines and Bases of the Brazilian Education (LDB) Law no. 4024/61; to identify the devices pedagogic of confirmation to the process of educational to become the teaching subjective. The subjects that put in motion of this walk are the following ones: How did the School Groups cultivate in your space the process to become subjective and discipline power? How did the curriculum biopolitic conform that process? What pedagogic devices did influence in the process to become subjective the educational work in Teacher Manoel Antonio de Castro Group School? It is a study of bibliographical and documental character. With support in the analysis of official documents of the public files of institutions as: City hall, Municipal and State Public File, Union of the professionals of Education of the Municipal distric and the Files of the Secretary of GEPMAC. The research happened in the historical period from 1940 to 1970, time of establishment of the Constitutions Federal of 1946 and 1967, of the Ordinance-law no. 8929 of the primary teaching and no. 8930 regarding the normal school and of the educational reform originating from of the Law of no. 4024 of 1961, besides to talk about the three ex-teachers of the School Group that were part of the analysis of this work. The study was based theoretically in Philosopher Michel Foucault’s writings of which it was used the analytic tools the can/to know relationships that it involves the analysis of the speech, relationships of can and the process to become subjective simultaneously. Starting from those analyses we considered that the history of the Brazilian education was and it is predominantly addressed by that Foucault calls superior administration starting from speeches of truths. Although the State intervenes in the social control of the education and of the educational work, these subjects are not hostages of the actions idealized in the ambit of the official power, because in your practices and involvement with the pedagogic devices execute institutional demands, but also, they react to them, be ignoring them or reacting or repelling the state action.